2023
DOI: 10.1111/tpj.16141
|View full text |Cite
|
Sign up to set email alerts
|

Type II arabinogalactans initiated by hydroxyproline‐O‐galactosyltransferases play important roles in pollen–pistil interactions

Abstract: SUMMARY Arabinogalactan‐proteins (AGPs) are hydroxyproline‐rich glycoproteins containing a high sugar content and are widely distributed in the plant kingdom. AGPs have long been suggested to play important roles in sexual plant reproduction. The synthesis of their complex carbohydrates is initiated by a family of hydroxyproline galactosyltransferase (Hyp‐GALT) enzymes which add the first galactose to Hyp residues in the protein backbone. Eight Hyp‐GALT enzymes have been identified so far, and in the present w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…According to our analyses and data in the literature, this gene may be related to the yield of maize because, according to Kaur et al (2023), hydroxyproline o-galactosyltransferase galt6 plays an important role in various stages of plant growth and development [73]. Moreira et al (2023) have reported that arabinogalactan proteins (AGPs) are hydroxyproline-rich, sugar-rich glycoproteins widely distributed in the plant kingdom [74]. The synthesis of their complex carbohydrates is initiated by a family of hydroxyproline galactosyltransferase (Hyp-GALT) enzymes, which add the first galactose to Hyp residues in the protein backbone.…”
Section: Discussionmentioning
confidence: 80%
“…According to our analyses and data in the literature, this gene may be related to the yield of maize because, according to Kaur et al (2023), hydroxyproline o-galactosyltransferase galt6 plays an important role in various stages of plant growth and development [73]. Moreira et al (2023) have reported that arabinogalactan proteins (AGPs) are hydroxyproline-rich, sugar-rich glycoproteins widely distributed in the plant kingdom [74]. The synthesis of their complex carbohydrates is initiated by a family of hydroxyproline galactosyltransferase (Hyp-GALT) enzymes, which add the first galactose to Hyp residues in the protein backbone.…”
Section: Discussionmentioning
confidence: 80%
“…A key area of research for the future is to understand how different AGPs and other HRGPs interact in the wall with each other and with carbohydrates, lignin, and proteins, and in those cases where the AGPs are direct signaling molecules to identify their ligand and receptor/co-receptor partners and signaling pathways. Physiological roles for some of the AGPs are just now being identified through molecular genetic analyses of biosynthetic mutants (reviewed in Moreira et al 2023 ).…”
Section: The 5 Major Polymers Of the Plant Cell Wallmentioning
confidence: 99%
“…The most inhibitory process in stk transcriptome was the glycoside catabolic process (GO:0016139). Glycosides are a wide range group of plant secondary metabolites with multifaceted roles in regulating growth, defense and reproduction in plants (Choi et al ., 2014; Kytidou et al ., 2020; Moreira et al ., 2023). Glycoside hydrolases are a family of enzymes responsible for the removal of specific sugar moieties from glycosides.…”
Section: Discussionmentioning
confidence: 99%